2020
DOI: 10.3390/ijerph17114030
|View full text |Cite
|
Sign up to set email alerts
|

Waiting Time between Breast Cancer Diagnosis and Treatment in Brazilian Women: An Analysis of Cases from 1998 to 2012

Abstract: Brazilian law requires that treatment for breast cancer begin within 60 days of diagnosis. This waiting time is an indicator of accessibility to health services. The aim of this study was to analyze which factors are associated with waiting times between diagnosis and treatment of breast cancer in women in Brazil between 1998 and 2012. Information from Brazilian women diagnosed with breast cancer between 1998 and 2012 was collected through the Hospital Registry of Cancer (HRC), developed by the National Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 21 publications
0
15
0
7
Order By: Relevance
“…It was demonstrated that preoperative waiting time might have influence on the oncological surgery [ 20 ]. The variation in waiting time might increase the psychological stress on patients, but provide more sufficient preoperative reservation of organic function especially in elderly patients, leading to the differences in surgical outcomes of breast cancer and prostate cancer [ 21 23 ]. Peng et al reported that the longer preoperative waiting time of gastric cancer patients contributed to the shorter postoperative hospital stay; however, longer waiting time had no impact on OS [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that preoperative waiting time might have influence on the oncological surgery [ 20 ]. The variation in waiting time might increase the psychological stress on patients, but provide more sufficient preoperative reservation of organic function especially in elderly patients, leading to the differences in surgical outcomes of breast cancer and prostate cancer [ 21 23 ]. Peng et al reported that the longer preoperative waiting time of gastric cancer patients contributed to the shorter postoperative hospital stay; however, longer waiting time had no impact on OS [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, proper and on-time The Government's commitment holds incredible importance in the timely management of cancer in general. As an example, the law in Brazil states that the time from diagnosis to treatment of breast cancer should be less than 60 days (Ferreira et al, 2020). In the United Kingdom, suspected cases of colorectal cancer have to be referred within two weeks (Thomas and Burnet, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of breast and cervical neoplasms, the mortality of other gynecological neoplasms (ovary, corpus uteri, and vulva), are not significantly affected by the performance and coverage of PHC units [29]. Thus, the assistance provided by the service in the face of other neoplasms is still unviable due to the few screening strategies that are available [30,31].…”
Section: Discussionmentioning
confidence: 99%